2021
DOI: 10.3847/2041-8213/ac2de6
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Forbush Decreases of Cosmic-Ray Electrons and Positrons with the Dark Matter Particle Explorer

Abstract: The Forbush decrease (FD) represents the rapid decrease of the intensities of charged particles accompanied with the coronal mass ejections or high-speed streams from coronal holes. It has been mainly explored with the ground-based neutron monitor network, which indirectly measures the integrated intensities of all species of cosmic rays by counting secondary neutrons produced from interaction between atmospheric atoms and cosmic rays. The space-based experiments can resolve the species of particles but the en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Apart from AMS observations distinguishing between GCRs particles according to their charge and mass, they are available up to very high rigidity (Aguilar et al 2021). Moreover, longduration space-based experiments with sophisticated detectors also resolve GCR species and their isotopic composition over a wide range of rigidity with a relatively high time resolution, for example, PAMELA (Adriani et al 2017), AMS (Aguilar et al 2021), and DAMPE (Alemanno et al 2021). Resolving the charge of GCRs is particularly helpful for studies of chargesign-dependent modulation over extended periods of time, which is what we focus on, especially over the HMF polarity reversal phase of Solar Cycle 24.…”
Section: Cosmic-ray Observationsmentioning
confidence: 99%
“…Apart from AMS observations distinguishing between GCRs particles according to their charge and mass, they are available up to very high rigidity (Aguilar et al 2021). Moreover, longduration space-based experiments with sophisticated detectors also resolve GCR species and their isotopic composition over a wide range of rigidity with a relatively high time resolution, for example, PAMELA (Adriani et al 2017), AMS (Aguilar et al 2021), and DAMPE (Alemanno et al 2021). Resolving the charge of GCRs is particularly helpful for studies of chargesign-dependent modulation over extended periods of time, which is what we focus on, especially over the HMF polarity reversal phase of Solar Cycle 24.…”
Section: Cosmic-ray Observationsmentioning
confidence: 99%
“…In particular, we focus on the Cosmic-Ray Electron (CRE) spectrum at low energies modulated by FD events (Figure 12 left-hand side panels). In 2021, an article based on one FD event detected by DAMPE in September 2017 was published [48]. Updated (preliminary) results based on 3 FD events (two in 2017 and one in 2021) were presented at this conference [49].…”
Section: Heliophysics: Forbush Decreasementioning
confidence: 99%
“…They also show that the helium and the proton amplitude are in agreement within the errors for each rigidity interval from 1 to 10 GV, which suggests that the exponential description of the rigidity dependence might be extrapolated to helium to some degree. Alemanno et al (2021) studied the 2017 September FD event with the CRE (cosmic-ray electron and positron) fluxes observed by the Dark Matter Particle Explorer (DAMPE) and also found that the amplitude can be well described by an exponential function in terms of energies. Thus, the rigidity dependence of FDs remains a very complicated problem and needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%